KESETARAAN GENDER DALAM PENDIDIKAN ISLAM PERSPEKTIF M. QURAISH SHIHAB - luqman hakim; Abdul Muhid (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2023)
The issue of gender equality and women's emancipation in the last decades has become an interesting topic of conversation among various groups, from academics, scholars, to the general public. Reality shows that women still get a lot of discriminatory treatment, subordination, and stereotyping, as well as gender injustice in society. Women do not get the same space as men in taking on public roles, especially in education. Where as in Islamic civilization there are many great female figures who have made major contributions in the fields of religion, economy, socio-culture, and education. Many people think that this happens due to an understanding of religious teachings and patriarchal culture in society. M. Quraish Shihab is a scholar and professor of Al-Qur'an interpretation who pays great attention to issues of gender equality and women's emancipation. Through research methods library research, this research article attempts to explore M. Quraish Shihab's thoughts on gender equality and women's emancipation in the interpretation of Al-Misbah and many other related scientific works. This paper concludes that Quraish Shihab provides a clear picture by interpreting the verses of the Qur'an about women and issues of gender equality based on the style of interpretation which has various interpretations that are relevant to the conditions of society to build a vision of gender equality within the framework of values. Islam to eradicate all forms of discrimination against women in various fields, especially in terms of Islamic education.